PENGEMBANGAN DAERAH KAMPUNG PESISIR MELALUI PENINGKATAN SARANA RT.06 KLANDASAN ULU - Syah Putra, Rulliannor; Alfiqri, Muhammad Diva; Zainun, Ahmad; Aditama, Fahrudin; Putri , Marshanda Aulia; Salsabila , Naurah; Pangestuti , Tria Puji; Santoso , Mallika Putri; Artanti, Tiara Harya (LPPM Institut Teknologi Kalimantan, 2024)
Facilities are facilities or tools needed to support a particular activity or activities. Developing facilities is one way to improve the quality of life of people in an area. Klandasan Ulu Village is one of the villages on the coast with a fairly dense population, but does not yet have adequate facilities for its people. The facilities in question include ablution places at local prayer rooms, alley signboards, and communal trash cans for residents. Therefore, it is necessary to develop facilities in the village to support the activities of the residents of Pesisir Village so that they can carry out their activities comfortably. The method for carrying out activities begins with discussions with local residents regarding the construction of rubbish bins, ablution places and sign boards along with their installation points. The results obtained during the activity were facilitating the community in disposing of rubbish easily, creating ablution facilities to facilitate worship activities, and creating sign boards as a useful information medium for the local community.